Recent progresses and challenges in aqueous lithium–air batteries relating to the solid electrolyte separator: A mini-review - Chen, Peng; Bai, Fan; Deng, Jun wen; Liu, Bin; Zhang, Tao (Frontiers in Chemistry, 2022)
Lithium air (Li-air) battery utilizes infinite oxygen in air to store or release energy by a semi-open cathode structure and bears an ultra-high theoretical energy density of more than 1000 Wh/kg. Therefore, it has been denoted as the candidate for next generation energy storage in versatile fields such as electric vehicles, telecommunications and special power supply. Among all types of Li-air batteries, aqueous Li-air battery bears advantages of high theoretical energy density of more than 1700 Wh/kg and does not have the critical pure oxygen atmosphere issues in non-aqueous lithium air battery system, which is more promising for the actual application. To date, great achievements have been done in materials design and cell configurations but critical challenges still remain in the field of solid electrolyte separator, its related lithium stripping/plating at lithium anode and catholyte design . In this mini-review, we summarized recent progress related to solid electrolyte in aqueous Li-air batteries focusing on both material and battery device development. Moreover, we proposed discuss and unique outlooks in improving solid electrolyte compatibility and battery performance, thus to the designing of aqueous Li-air battery with higher energy density and better cycle performance in the future.